Legal Aspects In The Making of The Buying Boarding Deed And The Power of Sale - Eric Reinaldo; Rusdianto Sesung (Faculty of Law, Merdeka University Surabaya, 2022)
The process of buying and selling land has a procedure that has been regulated in the legislation. In the process of buying and selling land, problems are often found, such as the inability to sign the deed of sale because it has not been paid off. One way to keep the binding on the object of sale and purchase is through the making of a PPJB deed and the power to sell. The function of PPJB and the power of attorney is to prevent the seller from committing fraudulent acts to the buyer by reselling the object's land to other prospective buyers. There have been criminal law cases in connection with the making of the PPJB deed and the power to sell which will be analyzed in this legal research. The formulation of the problem in this legal research is the procedure for making a sale and purchase binding deed and the power to sell, a juridical review of a criminal decision against a notary in making a sale and purchase deed and PPJB. That this legal research uses normative legal research and uses a conceptual approach, and a case approach as a means of supporting legal research. The benefits of this legal research are as a guide so that law enforcers have a better understanding of how notaries work and as a means of increasing knowledge.